(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study aims to nurture competitive nurses by applying the havruta learning method to nursing science classes and verifying the learning method’s effects on the competencies of learners. Method/Statistical Analysis: This study was conducted on 146 nursing students at Baekseok Culture University taking Community Nursing ? and Nursing Management. Havruta-style paired discussion was applied during the 15-week curriculum and students submitted activity journals. This study was designed as a descriptive research study consisting of self-directed learning competency, discussion competency, individual and collective creativity and a satisfaction survey. Self-directed learning competency was measured through 45 questionnaire items across three criteria. Findings: The results of this study show that among the 3 sub-criteria of self-directed learning, “learning practice” had the highest average score at 3.6 out of 5. The questionnaire item that scored the highest point(4.08) was “I complete tasks or work to see through to the end.” The average score of discussion competency was 3.35 out of 5. Communication skill competency consisting of adaptation, argument, and non-verbal communication had the highest average score at 3.54, while prediction competency had the lowest average score at 3.18. The average total score of discussion competency was 35.38, which indicates “middle” discussion competency. In terms of individual creativity, the questionnaire item regarding “intrinsic task motivation” scored the highest at 3.91, and the average score of collective creativity was 3.56. Regarding satisfaction with the havruta learning method, the item “I would strongly recommend the havruta learning method to my juniors,” scored the highest at 4.09. Improvements/Applications: The new havruta learning method, focused on havruta-style paired discussion, needs to be applied to nursing classes of all school years with continuity so as to prove the effects of the learning method.